Safety and effectiveness of ultrasound guided peripheral nerve blocks: audit at a tertiary care hospital - Asma Abdus Salam; Riffat Aamir; Robyna Irshad Khan; Aliya Ahmed; Azhar Rehman (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the safety and effectiveness of peripheral nerve blocks using ultrasound. Methods: All patients who received peripheral nerve blocks (PNB) as a part of their anaesthesia care, in two years were analysed retrospectively. The data included outcomes of PNB effectiveness, complications and limb conditions after block. PNB effectiveness was assessed by monitoring pain scores at rest and on movement and the requirement of co- analgesia. Complications like numbness, motor block, metallic taste, hypotension, respiratory depression were also assessed. Results: A total of 299 patients received ultrasound guided peripheral nerve blocks. Most common block performed was transversus abdominus plane block (TAP) block (46.5%) followed by supraclavicular block (16.7%). Most common complication observed in the recovery room after PNB was numbness 6.2%. Approximately 70% patients remained pain free; however 16% of the patients had moderate pain on movement at 12 hour post-operatively. Sedation score, sensory block and skin conditions were observed to be normal. Conclusion: This study shows that the complications associated with ultrasound guided regional anaesthesia (UGRA) are very few. With advancements in ultrasound guided technique, further studies are required to evaluate benefits and complications in comparison to conventional techniques. Keywords: Regional anesthesia, ultrasound guided blocks, peripheral nerve blocks Continuous....